How to deal with change to your job (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. We, humans, are creatures of habit and thrive in routine. Today we'll be talking about change in the workplace, and how to positively deal with changes to your job. The keyword here is positive. It's easy to reject change, especially at work. But if you quit your job at the smallest sign of change, you'd never build the work history or the rapport to have maximized the success of your career. In this track, we look at a number of coping strategies to help you manage change at work. Learning Objectives Learn active coping strategies in the face of change Learning to recognise and not fall into the trap of avoidance.